Anion receptors containing thiazine-1,1-dioxide heterocycles as hydrogen bond donors - Wang, Hong-Bo; Wisner, James A.; Jennings, Michael C. (Beilstein Journal of Organic Chemistry, 2010)
The synthesis, X-ray crystal structures and anion recognition properties of two receptors containing thiazine-1,1-dioxide heterocycles as hydrogen bond donating subunits are reported. The newly synthesized receptors display much different anion selectivities in acetone-d6 than N,N′-diphenyl-1,3-disulfonamidobenzene that was used as a comparison. The selectivity exhibited by one of the new receptors for chloride anions can be attributed to greater steric demand in the cleft formed, in part, by its terminal phenyl rings; an effect that is absent in the comparison receptor.
Keywords: anions; hydrogen bonds; receptors; sulfonamides; supramolecular chemistry